Effects of Combing Group Executive Functioning and Online Parent Training on School-Aged Children With ADHD: A Randomized Controlled Trial - Chu, Liting; Zhu, Peiying; Ma, Chenhuan; Pan, Lizhu; Shen, Li; Wu, Danmai; Wang, Yu; Yu, Guangjun (Frontiers in Pediatrics, 2022)
Objective The acceptance of drug treatment for younger children with attention-deficit/hyperactivity disorder (ADHD) in China remains low. Here, we explored the clinical benefits of a non-pharmaceutical intervention method combining a group and executive function training and an online parent training program, termed group executive functioning and online parent training (GEF-OPT), for school-aged students with ADHD through a randomized controlled trial. Method A total of 145 children (aged 6–8 years) were formally registered and randomized to the intervention group (n = 73) and waitlist group (n = 72). The enrolled children received eight sessions of GEF-OPT treatment, which consists of a hospital-based children executive function (EF) training program and an online parent training program. Treatment outcome was assessed by a parent/teacher report questionnaire and neurophysiological experiment. Results After eight sessions of intervention, children in the intervention group showed a significant improvement in inattentive symptom compared to the waitlist group (14.70 ± 4.35 vs. 16.03 ± 2.93; p = 0.024), but an insignificant difference in hyperactive-impulsivity (9.85 ± 5.30 vs. 10.69 ± 5.10; p = 0.913). Comorbid oppositional defiant disorder was significantly reduced in the intervention group (7.03 ± 4.39 vs. 8.53 ± 4.41; p = 0.035). Children in the intervention group had greater reduction in the scores of behavioral regulation index (inhibition, emotional control) and metacognition index (working memory, planning/organization, monitoring) in executive function than those in the waitlist group (p < 0.05). Significant effects were also found in learning problem of Weiss Functional Impairment Scale–Parent form and parental distress between two groups at post-treatment (p < 0.05). In line with this, the result of go/no-go task showed significant improvements in accuracy change (4.45 ± 5.50% vs. 1.76 ± 3.35%; p = 0.001) and reaction time change (47.45 ± 62.25 s vs. 16.19 ± 72.22 s; p = 0.007) in the intervention group compared with the waitlist group. Conclusion We conclude that participants in the GEF-OPT program improved outcomes for inattentive symptom, executive function, learning problems, and parental distress. GEF-OPT is a promising non-pharmaceutical therapeutic option for younger children. Trial Registration ChiCTR2100052803.